PERAN HUTAN KOTA GELORA BUNG KARNO SEBAGAI PENGHASIL OKSIGEN - Asri, Balqis Melza; Supriono, Bambang; Sasongko, Dwi Agus (Universitas Nusa Bangsa, 2023)
The increase of people population is the main factor in the growth of an urban area. Population growth will be followed by increasing ecological, economic and social needs. Urban development tends to cause a decrease in the quantity and quality of Green Open Space. The Gelora Bung Karno Urban Forest, which is part of the Green Open Space in Jakarta, is a place visited by many people. The aim of this research is to determine the amount of oxygen produced by the Gelora Bung Karno Urban Forest in one year. The method for calculating oxygen yield that is applied is by comparing the uptake of carbon and oxygen produced from the photosynthesis process. The results of the research showed that there were 49 individuals from 6 types of trees, namely Trembesi (Samanea saman), Ketapang (Terminalia catappa), Coconut (Cocos nucifera), Pulai (Alstonia scholaris), Jackfruit (Artocarpus heterophyllus), Eboni (Diospyros celebica). Apart from that, the city forest land is also covered with grass covering an area of 1.5 Ha. Gelora Bung Karno Urban Forest produces oxygen produced is 13,082,272.80 kg/year or the equivalent of providing oxygen for 42,668 visitors. The largest contribution comes from grass with 12,264,000 kg/year. The contribution of the Gelora Bung Karno Urban Forest to the oxygen needs of Central Jakarta residents is 3.52% of the total population.